ESSENTIAL SKILLS FOR EARLY CAREER RESEARCHERS - Roche, Joseph (Lecturer in education) (SAGE, 2022)
The perfect companion to support your development of the academic and professional skills you need as an early career researcher to help you thrive in academia. This practical book offers guidance on the essential skills you need to succeed as an academic researcher: work out how to thrive in academia while protecting your own wellbeing, learn how to develop discipline and structure in your academic writing, navigate the nuances of research funding applications, understand how to build professional development into your daily work, take a smart perspective on career progression. Designed to work across academic disciplines, each chapter includes lessons learned from published literature as well as perspectives from recent early career researchers to provide you with detailed insight applicable to diverse academic contexts." -- provided by publisher